Knowledge, attitude and practice of bio-medical waste management among private practitioners in Poonamallee taluk, Chennai - Dutta, Ruma; R., Prashanth; Parasuraman, Gomathy; Jain, Timsi; Raja, Dinesh; Dcruze, Lawrence (International Journal Of Community Medicine And Public Health, 2017)
Background: Inadequate and inappropriate knowledge regarding disposal of Bio-Medical Waste may have serious health consequences to those who handle it as well as can have a deleterious impact on the environment. The objective of the study was to assess the knowledge, attitude and practices about the various aspects of bio-medical waste (BMW) management among private practitioners of Poonamallee taluk, Chennai Methods: A community based cross-sectional study was conducted to assess the Knowledge, Attitude and Practices about the various aspects of Bio-Medical Waste (BMW) management among private practitioners of Poonamallee taluk, Chennai. The sample size was calculated as 171. Data was collected using a structured interview schedule among all private practitioners including dentists. Data was entered and analyzed by using IBM SPSS software Version 21. Results: 78.3% private practitioners were found to have adequate knowledge about the biomedical waste management rules. 76% private practitioners had knowledge regarding segregation of waste at source. 56.7% of practitioners segregated the BMW into different categories at source level and disposed in specified color coded containers. Conclusions: The importance of training regarding biomedical waste management needs emphasis; lack of proper and complete knowledge about biomedical waste management impacts practices of appropriate waste disposal.